Production of Bio-omega-3 eggs through the supplementation of extruded flaxseed meal in hen diet. Issue 1 (December 2015) - Imran, Muhammad; Anjum, Faqir; Nadeem, Muhammad; Ahmad, Nazir; Khan, Muhammad; Mushtaq, Zarina; Hussain, Shahzad
Abstract Background The full-fat flaxseed meal has obtained relatively new flourished concept as staple chicken feedstuff for the production of designer eggs. However, unprocessed flaxseed also encloses well documented anti-nutritional factors which are associated with growth depression of laying hens. The present research work was carried out to evaluate the impact of full-fat extruded flaxseed meal supplemented diets on productivity performance of hens and production of modified ω-3 fatty acids-enriched eggs. Methods The full-fat flaxseed meal was extruded at barrel exit temperature (140 °C), screw speed (160 rpm) and feed rate (25 kg/h) for reduction of anti-nutritional compounds. One hundred and sixty, Babcock hens (age 24 weeks old) were selected at random from a large flock and ten hens were placed in each of 16 wire-mesh pens. The experimental diets prepared by supplementation of extruded flaxseed at 10 %, 20 % and 30 % level were fed to hens along with control. Results The extruded flaxseed contained 86 % and 76 % less hydrocyanic compounds and tannin, respectively than the initial material. The hens fed with control diet consumed more feed, possessed heavy body weight and showed higher egg production as compared to hens fed on extruded flaxseed supplemented diets. The loss in body weight and egg production was recorded less for hens fed on 10 % extruded flaxseed supplemented diets as compared to those fed on 30 % extruded flaxseed supplemented diets. None of the experimental diets resulted in significant increase or decrease the total lipids and cholesterol content in egg yolk of hens. The extruded flaxseed supplemented diets resulted in a significant improvement of α-linolenic and docosahexaenoic acid in egg yolk with a concomitant reduction in arachidonic acid. The sensory scores were assigned higher to control eggs. Increasing level of extruded flaxseed in experimental diets decreased the scores for all sensory attributes of eggs. Conclusion The present study suggested that extruded flaxseed meal up to 20 % can be supplemented in the diets of hens for maximum deposition of α-linolenic acid and docosahexaenoic acid in egg yolk with acceptable detrimental effects on egg traits.